Improved estimates on global carbon stock and carbon pools in tidal wetlands - Xiaoguang Ouyang; Shing Yip Lee (Nature Communications, 2020)
Wetlands are global hotspots of carbon storage, but errors exist with current estimates of the extent of their carbon density. Here the authors show that mangrove sediment organic carbon stock has previously been overestimated, while ecosystem carbon stock has been underestimated.